The Effect of Premarital and Preconception Counseling on Prospective Fathers in Preventing Pregnancy Risk Factors at the Munjuljaya Community Health Center, Purwakarta Regency, Indonesia - Elma Theana; Leli Punamawati (International Journal of Health and Pharmaceutical (IJHP), 2026)
A healthy pregnancy is influenced not only by maternal preparedness but also by the support and readiness of prospective fathers. Insufficient knowledge among prospective fathers regarding premarital and preconception health may increase the risk of pregnancy complications, maternal anemia, stunting, and inadequate support for maternal health during pregnancy. Therefore, promotive and preventive efforts through premarital and preconception counseling are essential to improve prospective fathers' knowledge and preparedness in preventing pregnancy risk factors.This study aimed to determine the effect of premarital and preconception counseling on prospective fathers in preventing pregnancy risk factors in the working area of the Munjuljaya Community Health Center, Purwakarta Regency, Indonesia.This study employed a quantitative approach using a quasi-experimental design with a one-group pretest–posttest design. The intervention was administered to 30 prospective fathers in the working area of the Munjuljaya Community Health Center. Participants received premarital and preconception counseling focusing on knowledge, attitudes, and health behaviors related to pregnancy risk prevention. Data were analyzed using the Wilcoxon Signed-Rank Test with a significance level of 0.05.The findings showed that, before the counseling intervention, most respondents (60.0%) had poor ability to prevent pregnancy risk factors. After the intervention, 56.7% of respondents achieved a good level of pregnancy risk prevention. Statistical analysis demonstrated that premarital and preconception counseling significantly improved the knowledge, attitudes, health behaviors, and pregnancy risk prevention abilities of prospective fathers (p < 0.05).In conclusion, premarital and preconception counseling is an effective strategy for enhancing prospective fathers' readiness to support healthy pregnancies by improving their knowledge, attitudes, health behaviors, and ability to prevent pregnancy risk factors. Strengthening counseling services at primary healthcare facilities is recommended to optimize paternal involvement in maternal and child health programs.